The biography of a book: the Turku copy of the 1613 Mercator-Hondius Atlas - Impe, Steven van (Approaching religion, 2016)
In this article we look at the printing and publishing history of the 1613 edition of the Mercator-Hondius Atlas. Our main focus is on the editions published by the Hondius family in the early seventeenth century. We take a closer look at the 1613 Latin edition, focusing on one specific, previously unrecorded copy currently held by the Donner Institute in Turku. We relate our findings to the more general issues concerning the production, context and history of the atlas.